Factors influencing patient’s satisfaction level on foodservice at Hospital Universiti Sains Malaysia (HUSM) Kubang Kerian, Kelantan / Nurul -Iz Mohd Napi - Mohd Napi, Nurul -Iz (2020)
The objective of this analysis is to analyze and evaluate the factors that affect customer satisfaction at Hospital Universiti Sains Malaysia (HUSM) on food service. Employee efficiency, communication skills of the workers, convenience, suitability & cleanliness of the dishware, time of distribution of food, attitude and behavior of the workers and quality of food are considered as independent variables and customers satisfaction use as dependent variable. The study is quantitative in nature, and the convenience sampling method was used using a survey questionnaire for data collection, and the sample size for this study was caped 303 respondents. The findings from this study will be useful in deciding to increase patient satisfaction with the food services for hospital administrators and the food (nutrition) departments. In the other side, the findings will also be used for benchmarking the quality of the hospital's food services with other hospitals, and for analyzing potential changes in the quality of the food services.